1996
DOI: 10.1089/jir.1996.16.589
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Interleukin-6 Gene Expression to Immunologic Features in Patients with Cardiac Myxomas

Abstract: Cardiac myxomas, the most common primary heart tumors in adults, show a variety of clinical manifestations and laboratory findings correlated with elevated interleukin-6 (IL-6) serum concentration. The aim of this study was to determine the expression of IL-6 mRNA in myxoma tissue as a cause to frequent immunologic abnormalities in patients with such tumors. In our centers, we analyzed 17 surgically resected myxomas using the polymerase chain reaction (PCR) and found increased IL-6 mRNA expression in 14 of 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Size ranges from 2 to 3 mm to 15 cm and can weigh as much as 450 g. Microscopically, the myxoma is composed of stellate, fusiform, or plump cells and cytologically bland mesenchymal cells in a myxoid stroma. The cells are arranged singly, in cords, or in the form of rings [9][10][11]. In our series, myxomas had a higher preponderance in female patients.…”
Section: Commentmentioning
confidence: 88%
“…Size ranges from 2 to 3 mm to 15 cm and can weigh as much as 450 g. Microscopically, the myxoma is composed of stellate, fusiform, or plump cells and cytologically bland mesenchymal cells in a myxoid stroma. The cells are arranged singly, in cords, or in the form of rings [9][10][11]. In our series, myxomas had a higher preponderance in female patients.…”
Section: Commentmentioning
confidence: 88%
“…The IL-6 was highly expressed in the myxomatous cells in an immunohistochemical study 3) . Serum IL-6 level is usually elevated in patients with CM, and is normalized immediately after surgical removal of CM 5) . Mendoza,et al 3) demonstrated that there was a posi- tive correlation between serum IL-6 level and size of CM, and that overproduction of IL-6 by myxomatous cell was associated with tumor recurrence or distal embolization 3) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that embolic myxomas constitutively express high levels of IL-6. 9 Autocrine production of IL-6 may represent one of the mechanisms responsible for the excessive MMP synthesis in embolic myxomas. Increased MMP delivery in the medium of embolic myxoma cultures also suggests that the increase of MMP plasma levels may represent an additional peripheral marker to identify patients at risk of embolism among those cases in which echocardiographic criteria are not characteristic.…”
Section: Mechanisms Regulating Mmp Synthesis In Myxoma Cellsmentioning
confidence: 99%
“…[1][2][3][4][5]8 Because most myxomas are left atrium-located, emboli prevalently involve peripheral districts, in particular cerebral arteries, including the retinal artery. [1][2][3]8 Echocardiographic polypoid and irregular macroscopic aspects, 3,5 changes in the composition of the myxomatous matrix, 6 as well as the autocrine production of interleukin (IL)-6 9 have been considered, but the real causes of embolism in cardiac myxomas are still unknown. Matrix metalloproteinases (MMPs) are a large family of zinc-dependent proteolytic enzymes that are responsible for ECM remodeling in both normal and pathological processes.…”
mentioning
confidence: 99%